Analysis of small game areas of 4vs4 and 7vs7 in Spanish professional football - Caro, O.; Fradua, L.; Zubillaga, A. and Fernandez-Navarro, J. (Proceedings of the 2nd International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2014)
The aim of this study was to analyse the reduced space game situations that appear during competition in soccer considering interactions with a small number of players involved. The Amisco system was employed to collect the dimensions of playing areas of different situations from competition in order to extrapolate the results to the appropriate training drills design in reduced space. 8,477 4v4 and 7v7 game situations were collected for the study. Width, length and individual playing area were registered from these situations. The influence of the zone of the pitch in the configuration of these spaces was also considered. The results showed that the dimensions of the areas designed for training drills are larger than those in competition. The influence of the zone of the pitch is also significant, mainly in 4v4 situations. This should be considered to adjust the training drills design depending on the intended tactical aim, directly associated with the zone of the pitch where the tr aining drill is developed.